Experiences of Person‐Centred Care Among Nurses in COVID‐19 Wards: A Qualitative Study - Myoungsuk Kim; Yongmi Lee; Hyun‐Ju Kang (Nursing Open)
ABSTRACT Aim While there is extensive research on nurses' experiences in caring for COVID‐19 patients, studies focusing on person‐centred care in this context remain limited. This study aimed to obtain a thorough understanding of the meaning and essence of person‐centred care experienced by nurses in COVID‐19 wards in South Korea. Design This study adopted a qualitative research design. Methods Data were collected from April 2022 to February 2023 using one‐on‐one in‐depth interviews with nine nurses working in COVID‐19‐designated hospitals; these data were analysed using content analysis. This study adhered to the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Results The five categories were: encountering barriers between nurses and patients, the conflict between principles and dignity, providing individualised care even under controlled circumstances, providing care in a therapeutic community relationship and desiring stable care even in a crisis. Conclusion This study examined nurses' challenges and experiences in delivering person‐centred care during the COVID‐19 pandemic. Despite the conflict between infection control guidelines and individual patient needs, nurses sought to address patients' psychological and physical challenges while overcoming COVID‐19 together, leading to satisfaction for both patients and nurses. Systemic support and education are essential to sustain person‐centred care, and this study provides valuable insights for improving nursing practice in crisis situations. Patient or Public Contribution No patient or public contribution.